Practical management of patients with hematological diseases during the COVID-19 pandemic in Japan - Hagihara, Masao; Ohara, Shin; Uchida, Tomoyuki; Inoue, Morihiro (International journal of hematology, 2021)
Polymerase chain reaction (PCR) tests cannot always detect the SARS-CoV-2 virus, possibly due to differences in sensitivity between sample types. Under these circumstances, immunochromatography may serve as an alternative method to detect anti-SARS-CoV-2 IgG antibodies that indicate a history of infection. In our analysis of patients with severe COVID-19 infection, we found that 14 of 19 serum samples were positive for IgG antibodies, whereas 6 of 10 samples from patients with asymptomatic or mild cases were negative. Two patients with immune thrombocytopenia who were treated with prednisolone experienced aggressive COVID-19-related respiratory failure and eventually died. Patients not in remission and those who received steroid-based chemotherapy had a higher risk of death, and patients with lymphoid malignancies including lymphoma and myeloma died in larger numbers than those with myeloid malignancies. A stricter cohorting strategy based on repeat PCR tests or isolation to a private room should be adopted in routine care in hematology departments to prevent viral spread to the environment.